The multi‐component Hekla Ö Tephra, Iceland: a complex widespread mid‐Holocene tephra layer. (3rd January 2020) - Jónsson, Daníel Freyr; Gudmundsdóttir, Esther Ruth; Larsen, Gudrún; Óladóttir, Bergrún Arna; Erlendsson, Egill; Eddudóttir, Sigrún Dögg; Sigmarsson, Olgeir
ABSTRACT: Large Plinian eruptions from Hekla volcano, Iceland, produce compositionally zoned tephra used as key markers in tephrochronology. However, spatial variations in chemical composition of a tephra layer may complicate its identification. An example is the 5950–6180 cal a bp Hekla Ö tephra layer, which shows compositional spread from rhyolite, dacite and andesite to basalt. In soil sections north of Hekla, the SiO2 content of the tephra glass reaches 76 wt% in the lowest unit of the Hekla Ö deposit and decreases to 62–63 wt% in the uppermost unit. Intermingled within the whole deposit are basalt tephra grains having 46–47 wt% SiO2 . The composition of the basalt glass includes primitive basalt and a more evolved basalt (MgO >6 and <6 wt%, respectively). Together with literature data, the Hekla Ö tephra and the so‐called T‐Tephra/Hekla‐T are most likely from contemporaneous eruptions of different vents on the Hekla volcanic system, forming a single important marker tephra (Hekla ÖT) deposited over 80% of Iceland. Identification is complicated by its spatial compositional heterogeneity, such as systematic decrease in SiO2 content from the east to the west of Hekla volcano. Consequently, an individual tephra layer from a large explosive eruption can have different composition at different locations. © 2020 John Wiley & Sons, Ltd.